PENERAPAN MEDIA POP UP BOOK UNTUK MENINGKATKAN KETERAMPILAN PROSES IPA PADA MAHASISWA PGSD - PRATIWI, INDAH; AMELIA, CHAIRUNNISA (Jurnal Ilmiah Aquinas, 2020)
This study aims to determine the improvement of science process skills possessed students by using the PopUp Book learning media. The method used in data collection is documentation, observation and tests. In this study, researchers or lecturers use pop-up media that aiming to see an enchance in the science learning process skills of PGSD students. This study can be seen from the average assessment classically to see the science process skills possessed by students in each indicator of the science process skills. In 1st indicator, the skills to observe before using the media are 49.1% and after using the media are 82.9%.Â In the 2nd Indicator, the skills of formulating a hypothesis before using the media are 42.4% and after using the media are 79.5.%. In the 3rd Indicator, the skills of planning an experiment before using the media are 46.2% and after using the media are 85.7%. In 4th indicator,Â the skills of conducting experiments before using the media are 54.3% and after using the media are 90.5%. In the 5th Indicator,Â the skills to predict before using the media are 43.3% and after using media are 80.9%. In the 6th indicator, the skills of applying concepts before using media are 41.9% and after using media are 78.6%. In the 7thindicator, communication skills before using media are 41.9% and after using media are 90%. The result shows that the Pop Up Book learning media can improve the science process skills of PGSD students.